PENGARUH CUSTOMER EXPERIENCE DAN BRAND IMAGE TERHADAP CUSTOMER SATISFACTION DAN CUSTOMER LOYALTY PADA PENGGUNA APLIKASI MOBILE KOPI KENANGAN DI JABODETABEK - Puspa Nuraini Putri; Osly Usman; Nofriska Krissanya (Jurnal Riset Multidisiplin Edukasi, 2026)
This study aims to analyze the direct influence of customer experience dimensions, comprising cognitive, affective, relational, and sensorial experience, as well as brand image, on customer satisfaction and customer loyalty among Kopi Kenangan mobile application users in Jabodetabek. Primary data were collected from 226 active users through an online questionnaire using purposive sampling and analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS) with SmartPLS 4.0. Of 11 hypotheses tested, 9 were accepted. Cognitive experience emerged as the strongest predictor of satisfaction (β=0.297), followed by brand image (β=0.254), affective experience (β=0.191), and relational experience (β=0.161). Relational experience exerted the largest direct effect on loyalty (β=0.187), while customer satisfaction was the overall strongest loyalty predictor (β=0.273). Sensorial experience was non-significant in both paths, indicating its transition to a hygiene factor at the current stage of app maturity. These findings offer actionable implications for digital F&B companies in optimizing customer experience design and brand management.